Contemporary issues in estuarine physics - Valle-Levinson, A. (Arnoldo) (Cambridge : Cambridge University Press, 2010)
Estuaries are of high socioeconomic importance with 22 of the 32 largest cities in the world located on river estuaries. Estuaries bring together fluxes of fresh and saline water, as well as fluvial and marine sediments, and contain high biological diversity. Increasingly sophisticated field observation technology and numerical modeling have produced significant advances in our understanding of the physical properties of estuaries over the last decade. This book introduces a classification for estuaries before presenting the basic physics and hydrodynamics of estuarine circulation and the various factors that modify it in time and space. It then covers special topics at the forefront of research such as turbulence, fronts in estuaries and continental shelves, low inflow estuaries, and implications of estuarine transport for water quality. Written by leading authorities on estuarine and lagoon hydrodynamics, this volume provides a concise foundation for academic researchers, advanced students and coastal resource managers.
Definition and classification of estuaries -- Estuarine salinity structure and circulation -- Barotropic tides in channelized estuaries -- Estuarine variability -- Estuarine secondary circulation -- Wind and tidally driven flows in semienclosed basin -- Mixing in estuaries -- The dynamics of estuary plumes and fronts -- Low-inflow estuaries: hypersaline, inverse, and thermal scenarios -- Implications of estuarine transport for water quality.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Estuaries; Estuaries -- Hydrodynamics